Urban and regional data management : UDMS Annual 2013 : proceedings of the Urban Data Management Society Sumposium 2013, London, United Kingdom, 29-31 May 2013 /: UDMS Annual 2013 : proceedings of the Urban Data Management Society Sumposium 2013, London, United Kingdom, 29-31 May 2013. ([2013]) - Unknown
No abstract available